Incidental Cardiac Findings on Thoracic Imaging. Issue 4 (November 2013) - Kok, Hong Kuan; Loo, Bryan; Torreggiani, William C.; Buckley, Orla
The cardiac structures are well seen on nongated thoracic computed tomography studies in the investigation and follow-up of cardiopulmonary disease. A wide variety of findings can be incidentally picked up on careful evaluation of the pericardium, cardiac chambers, valves, and great vessels. Some of these findings may represent benign variants, whereas others may have more profound clinical importance. Furthermore, the expansion of interventional and surgical practice has led to the development and placement of new cardiac stents, implantable pacemaker devices, and prosthetic valves with which the practicing radiologist should be familiar. We present a collection of common incidental cardiac findings that can be readily identified on thoracic computed tomography studies and briefly discuss their clinical relevance.